Higher adherence to the Mediterranean Diet is associated with lower micronutrient inadequacy in children: the SENDO project - Asier Oliver Olid; Elise Fabios; Lorena García-Blanco; Jose Manuel Moreno-Villares; Miguel Ángel Martínez-González; Nerea Martín-Calvo (Cambridge University Press, 2024)
Abstract Objective: To assess whether the Mediterranean Diet (MedDiet) is associated with lower micronutrients inadequacy in a sample of Spanish preschoolers. Design: We conducted a cross-sectional study with 4-5-year-old children participating in the SENDO project. Information was gathered through an online questionnaire completed by parents. Dietary information was collected with a previously validated semi-quantitative FFQ. The estimated average requirements or adequate intake levels as proposed by the Institute of Medicine were used as cut-off point to define inadequate intake. Statistical analyses: Crude and multivariable adjusted estimates were calculated with generalised estimated equations to account for intra-cluster correlation between siblings. Participants: We used baseline information of 1153 participants enrolled in the SENDO project between January 2015 and June 2022. Main outcomes measures: OR and 95 % CI of presenting an inadequate intake of ≥ 3 micronutrients associated with the MedDiet. Results: The adjusted proportion of children with inadequate intake of ≥ 3 micronutrients was 27·2 %, 13·5 % and 8·1 % in the categories of low, medium and high adherence to the MedDiet, respectively. After adjusting for all potential confounders, children who had a low adherence to the MedDiet showed a significant lower odds of inadequate intake of ≥ 3 micronutrients compared to those with a high adherence (OR 9·85; 95 % CI 3·33, 29·09). Conclusion: Lower adherence to the MedDiet is associated with higher odds of nutritional inadequacy.